Girls take over: Long-term impacts of an early stage education intervention in the Philippines - Yamauchi, Futoshi; Liu, Yanyan (International Food Policy Research Institute, 2011)
This paper examines the long-term impacts of improved school quality at the elementary school stage on subsequent schooling investments and labor market outcomes using unique data from a recent survey that tracked students in the Philippines. Empirical results, based on a comparison of students who graduated from treatment and control schools before and after a school intervention, show significant differences in subsequent schooling investments, migration, and labor market earnings between females and males. That is, females study more (relative to males) and tend to migrate and earn more if they receive high-quality educational investments at an early stage. The above results are consistent with females' greater incentives to study, driven by their higher returns to schooling, especially after high school completion, observed in the labor market.